The Different Polishing Systems Effect on Ormocer and Supranano Spherical Filler Composite Resin Surface Roughness - Regia Aristiyanto; Safira Salsabila; Alisa Dani Hayuningtyas (Denta Journal Kedokteran Gigi, 2023)
Background: The polishing procedure is an essential step in composite resin restoration. There are two types of polishing systems, which are one-step and multi-step polishing systems. Purpose: This study aimed to identify the effect of different polishing systems on the surface roughness of ormocer and supranano spherical filler composite resin. Material and Methods: This study was conducted in an experimental laboratory. The specimens were ormocer and supranano spherical filler composite resin filled in a cylindric metal mold. The total of specimens was thirty-two (n=32) of each composite resin. Each composite resin specimen was divided into four groups, then polished using PoGo (group 1 – one-step polishing system), Optrapol (group 2 – one-step polishing system), Sof-lex (group 3 – multistep polishing system), and Optidisc (group 4 – multistep polishing system). Specimens were incubated at 37℃ for 24 hours. Subsequently, specimens were assessed with a stylus profilometer surfcorder SE 1700. Data were analyzed using an independent t-test and one-way ANOVA. Result: There was a significant difference in surface roughness of the one-step and multistep groups (p ≤ 0.05). The lowest surface roughness value was in the Sof-Lex disc group (0.4026μm), and the highest surface roughness was in the PoGo group (1.1036μm). Conclusion: Based on composite resin, supranano spherical filler had less surface roughness than ormocer (p ≤ 0.05). Furthermore, both ormocer and supranano spherical filler polished using a multistep polishing system had lower surface roughness than those polished using a one-step polishing system.